Revisitando, a Contrapelo, a herança autoritária brasileira: a questão agrária no teatro de Oduvaldo Vianna Filho - Rosangela Patriota Ramos; Alcides Freire Ramos (Confluenze, 2023)
We live in dark times in Brazil. Times marked by the reverberation of authoritarian ideas and slogans, especially those based on the legacy of the Military Dictatorship (1964-1985). In this article, we will discuss how the dramaturgy of Oduvaldo Vianna Filho (known as Vianinha) dealt with the struggle for land, in order to shed light on proposals that opposed Brazilian military authoritarianism.